Root coverage using a connective tissue graft with epithelial striation in combination with enamel matrix derivatives - a long-term retrospective clinical interventional study - Knut Adam; Ingmar Staufenbiel; Werner Geurtsen; Hüsamettin Günay (BMC, 2019)
Abstract Background The application of a connective tissue graft with epithelial striation (CTG-ES) has been shown to improve the outcome of root coverage (RC) using the coronally advanced flap (CAF) and adjunctive administration of enamel matrix derivatives (EMD). Aim of the present study was to evaluate the long-term (mean: 16.19 ± 1.80 years, range: 13 to 18 years) stability of this treatment method with special focus on the location of the gingival margin and the width of keratinized tissue (WKT). Methods 16 patients (10 female, 6 male, aged 35.36 ± 14.70 years at surgery) with 25 Miller class I or II gingival recession (GR) defects were treated using the CAF combined with the CTG-ES and EMD. The clinical measurements recorded at baseline (t0), 6 months (t1), and 13 to 18 years (t2) after surgery included recession depth (RED), probing pocket depth (PPD), clinical attachment level (CAL), and WKT. In addition, the number of sites with complete RC (CRC) and the mean RC (MRC) were documented at t1 and t2. The statistical analysis was performed using a linear mixed model. Results The RED (t0: 4.52 ± 1.56 mm; t1: 0.36 ± 0.76 mm; t2: 0.30 ± 0.60 mm) and CAL (t0: 6.16 ± 1.62 mm; t1: 1.86 ± 0.87 mm; t2: 1.54 ± 0.92 mm) were significantly reduced at t1 and t2 compared to t0 (p <  0.001). The PPD was significantly reduced at t2 compared to t0 (p = 0.016). The WKT (t0: 1.18 ± 1.28 mm; t1: 3.26 ± 0.98 mm; t2: 4.26 ± 1.83 mm) significantly increased from t0 to t1, from t0 to t2 (p <  0.001) and from t1 to t2 (p = 0.007). A CRC was recorded at 19 sites (76.0%) at t1 and t2. The MRC was 93.6 ± 12.8% at t1 and 93.3 ± 13.3% at t2. Conclusions The use of the CAF combined with CTG-ES and EMD leads to stable long-term outcomes on teeth with Miller Class I or II GR defects. The CTG-ES represents a hybrid graft with increased position stability and advantageous properties for the healing process. We assume that the ES is responsible for the increase of the WKT.